ANALISIS MAKNA LEKSIKAL DALAM CERPEN MELEWATI MAKAM KARYA AGUS BUDI WAHYUDI - Kurniani; Yunita Puspita Sari; Dedi Febriyanto; Dea Anisa; Musalamatul Husna (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research aims to analyze how the author uses lexical meaning to create the story's atmosphere, depict characters, and convey messages in the short story Melewati Makam by Agus Budi Wahyudi. The research was conducted using a descriptive qualitative approach with the lexical semantic meaning analysis method. The data collected included words, phrases, clauses, and sentences containing lexical meaning, obtained through literature review, note-taking, categorization, and presentation in the form of analysis tables. The findings of this research show that lexical meaning plays a significant role in clarifying the atmosphere related to struggle, love, longing, and sacrifice, as well as strengthening the narrative and the reader's perspective. Lexical meaning also helps readers understand the historical context, conflict, and characters' emotions, thereby enhancing the linguistic quality and depth of meaning in the short story.